Biological crusts increase soil microbial biomass and alter bacterial and fungal community compositions under pine restored over ten years in a Pisha sandstone soil - Le, Qi; Ru, Meng; Weibo, Ren; Min, Zhang; Wentao, Mi; Ting, Yuan; Yaling, Liu; Feng, Yuan (Frontiers in Ecology and Evolution, 2025)
Drylands cover approximately 40% of the global terrestrial area. These regions face multiple challenges, including water scarcity, soil erosion, and declining biodiversity, which significantly undermine soil fertility and ecosystem stability. Biological soil crusts (biocrusts) are widely recognized as key components in arid and semi-arid regions. Due to their unique structure and functions, biocrusts can significantly improve soil structure, enhance soil nutrient accumulation and cycling, and mitigate soil erosion, thereby providing critical support for ecological restoration and sustainable development. This study investigated variations in soil properties, bacterial and fungal community structures, and the relationships between soil properties and microbial communities in biocrusts under pine forests. These pine forests have been utilized for soil and water conservation over a ten-year period of ecological restoration in the Pisha sandstone area. Compared to bare ground, soil available phosphorus was 0.96 and 1.79 times higher in cyanobacterial and moss biocrusts, respectively, while soil available potassium was 1.44 and 2.34 times higher, respectively. These abundant soil nutrients provide a carbon source for microorganisms, promoting the growth and metabolic activity of soil microorganisms, thereby significantly enhancing soil microbial diversity and biomass. Biocrusts also enhanced soil urease and invertase activities. Soil microbial biomass carbon was 2.65 and 8.19 times higher in cyanobacterial biocrusts and moss biocrusts, respectively, compared to bare ground, and soil microbial biomass nitrogen was 5.05 and 11.07 times higher, respectively. Additionally, the Observed Species Richness Index and Abundance-based Coverage Estimator Index of bacterial and fungal microorganisms in moss biocrusts were significantly higher than those in bare ground and cyanobacterial biocrusts. Soil pH, copper, microbial biomass carbon, and microbial biomass nitrogen are key environmental factors influencing soil microbial communities. Biocrusts significantly improve soil quality in the Pisha sandstone area by enhancing the soil properties. This not only strengthens the stability and sustainability of the ecosystem but also provides critical support for improving ecosystem productivity and environmental quality.